Analisis Financial Distress Perusahaan Transportasi Pada Masa Pandemi Covid-19 Menggunakan Analisis Model Altman Z Score dan Zmijewski - Salsabilla Salsabilla; Kurnia Hamidah; Zahra Putri Nabilla; Rayhan Fadlan (Jurnal Riset Akuntansi, 2023)
The purpose of this study was to analyze the financial distress of companies in the road transportation subsector listed on the IDX. This type of research is quantitative research. The population in this study were road transportation sub-sector companies listed on the Indonesia Stock Exchange in 2020 and 5 samples were taken using purposive sampling. Data obtained from financial reports published on the website www.idx.co.id with a time period of 2020. The findings of this study indicate that based on the two methods used, there are 2 companies that are in a healthy condition, namely PT Blue Bird Tbk and PT Eka Sari Lorena Transportasi Tbk. A total of 2 companies are included in unhealthy conditions, namely Steady Safe Tbk and Express Transindo Utama Tbk. The remaining 1 company that has different analysis results between the two methods used, namely PT WEHA Transportasi Indonesia Tbk.